(untitled) (International Journal of Mathematics and Physics, 2016)
The analytics was implemented for the scattering processes with channel spin structure 1/2, 3/2 and 5/2. For the first time the parameterization of differential cross sections by orbital momentums l = 0, 1, 2, … for the quartet and quintet spin channels has been performed. The presentation is given in a universe form and may be applied for the phase shift analyses for the scattering of nuclei or elementary particles. Same amplitudes are used in the construction of the polarization characteristics as vector and tensor polarization. The following isotopes are in field of interests: 7B(3/2-), 9B(3/2-), 11B(3/2-), 12B(1+), 13B(3/2-), 5Li(3/2-), 6Li(1-), 7Li(3/2-), 9Li(3/2-), 10Li (1-), 9C(3/2-), 11C(3/2-) and protons, neutrons, deuterons as impact particles.